PENERAPAN STRATEGI INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AQIDAH DAN AKHLAK KELAS VII D DI SATUAN PENDIDIKAN MU’ADALAH WUSTHO MAJLIS TAFSIR AL- QUR’AN KARANGANYAR TAHUN AJARAN 2024-2025 - Nastain, Abdul; Sukari, Sukari (Jurnal Manajemen Pendidikan, 2025)
The subject of Aqidah and Akhlak in Islamic education contains several thought constructs that aim to provide religious knowledge for students. This study aims to improve students’ learning outcomes in the Aqidah and Akhlak subject through the implementation of the Index Card Match strategy in Class VII D at Satuan Pendidikan Mu’adalah Wustho Majlis Tafsir Al Qur’an Karanganyar in the academic year 2024-2025. The research employed Classroom Action Research (CAR) method using the Kemmis and Taggart model, which consists of the stages of planning, action, observation, and reflection. The study was conducted in two cycles, where each cycle consisted of two meetings. The results of the study showed that the implementation of the Index Card Match strategy was able to enhance student activity and learning outcomes. In the pre-action stage, only 57% of students met the Minimum Completeness Criteria (KKM). In the first cycle, the percentage of students who met the KKM increased to 77%. Furthermore, in the second cycle, this percentage rose again to 88%. The Index Card Match strategy proved to be effective in creating a more interactive and enjoyable learning atmosphere, which in turn encouraged students to be more active and confident during the learning process.